2013
DOI: 10.1103/physrevlett.111.266101
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging of Individual Dopant Atoms inSrTiO3

Abstract: We report on three-dimensional (3D) imaging of individual Gd dopant atoms in a thin (∼2.3  nm) foil of SrTiO3, using quantitative scanning transmission electron microscopy. Uncertainties in the depth positions of individual dopants are less than 1 unit cell. The overall dopant concentration measured from atom column intensities agrees quantitatively with electrical measurements. The method is applied to analyze the 3D arrangement of dopants within small clusters containing 4-5 Gd atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
100
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 38 publications
2
100
1
Order By: Relevance
“…Another source of I Sm;Sr variations is the Sr doping. The Sr dopants have a lower Z than the host (Sm); thus, Sr-containing columns show lower image intensity, with the column intensity depending on the number of Sr atoms, their depth locations, the total number of atoms in the column, and the STEM parameters [28,[38][39][40]. The white arrows in the I Sm;Sr maps indicate selected columns that show significantly reduced intensities relative to those of nearest-neighbor Ti-O columns, which have similar thicknesses.…”
mentioning
confidence: 99%
“…Another source of I Sm;Sr variations is the Sr doping. The Sr dopants have a lower Z than the host (Sm); thus, Sr-containing columns show lower image intensity, with the column intensity depending on the number of Sr atoms, their depth locations, the total number of atoms in the column, and the STEM parameters [28,[38][39][40]. The white arrows in the I Sm;Sr maps indicate selected columns that show significantly reduced intensities relative to those of nearest-neighbor Ti-O columns, which have similar thicknesses.…”
mentioning
confidence: 99%
“…Furthermore, most techniques cannot provide direct information about atom relaxations around a point defect even though these are crucial for many properties.Previously, we have shown that HAADF-STEM can provide three-dimensional information of the location of individual dopant atoms in SrTiO3 from a single image [1]. The number of dopant atoms in a column and the depth position information are extracted using quantitative STEM, by comparing the experimental column intensities with calculations for all possible dopant configurations, and determining the most probable dopant position given an experimentally determined noise function.…”
mentioning
confidence: 99%
“…An important complementary method in STEM is position averaged convergent beam electron diffraction (PACBED), which is highly sensitive to information that cannot easily be obtained from HAADF-STEM images, such as small displacements of atom or tilts of oxygen octahedra in perovskite materials [2,3]. In this presentation, we will discuss our recent [4,5] work in applications of quantitative HAADF-STEM and PACBED to pertinent problems in materials science.Our first example concerns the determination of the three-dimensional location of individual Gd dopant atoms in SrTiO3 [4]. The method is based on using quantitative comparisons of experimental and calculated image intensities.…”
mentioning
confidence: 99%
“…Our first example concerns the determination of the three-dimensional location of individual Gd dopant atoms in SrTiO3 [4]. The method is based on using quantitative comparisons of experimental and calculated image intensities.…”
mentioning
confidence: 99%